Cultivating Environmental Sustainability Awareness in Students Through ECO-SETS: Implementation of Science, Environment, Technology, and Society (SETS)-Based Worksheets on Climate Change Topics - Patriot, Evelina Astra (Integrated Science Education Journal, 2026)
Purpose of the study: This study aims to develop the ECO-SETS Worksheet (Environment and Climate Oriented through Science, Environment, Technology, and Society), an innovative student worksheet that integrates the SETS approach with simple coding simulations to train students’ ESA on climate change topics. Methodology: The research employed the ADDIE development model, consisting of five stages. The study involved Grade X and XI students from several schools in South Sumatra. Data collection included teacher interviews, expert validation by three experts, student practicality questionnaires involving nine students, and effectiveness testing through pretest–posttest assessments with 60 respondents. Instruments consisted of Likert-scale questionnaires, open-ended feedback forms, and concept mastery tests. Data were analyzed using the Guttman scale for validity, the Likert scale for practicality, and N-gain and t-tests for effectiveness. Main Findings: The results indicate that ECO-SETS LKPD is highly valid, with average validation scores of 90.7%, and very practical, with student response scores of 97.14% (one-to-one trial) and 96.50% (small-group trial). In terms of effectiveness, the LKPD significantly improved students’ environmental sustainability awareness, evidenced by an N-gain score of 0.65 in the experimental class and statistically significant differences compared to the control group. Novelty/Originality of this study: The novelty of this study lies in the integration of SETS-based contextual learning with simple coding simulations within a structured LKPD framework, bridging environmental education and computational thinking. This integrative approach not only strengthens conceptual understanding but also equips students with adaptive skills to address real-world environmental challenges, offering a new direction for sustainable science education.